Establishment of Significant Correlation between Seasonal Physicochemical parameters and Zooplankton Diversity in Saheb Bandh, at Purulia, West Bengal - Chattopadhyay, Dhrubajyoti; Panda, Suvendu (International Journal of Scientific Research in Biological Sciences, 2022)
In the aquatic ecosystem, zooplankton plays a crucial role. Its distribution and assortment, however, are driven by several physicochemical parameters in an association. The present study, on the zooplankton community, was carried out between March 2021 to February 2022 for one year at the Saheb Bandh, Purulia West Bengal, to unveil the critical association between zooplankton and physicochemical parameters. For this purpose, Water samples were also tested for zooplankton community composition and density. The parameters correlated positively with several zooplankton groups. A variety of physicochemical characteristics were measured for the water samples. Totally 4 taxonomic groups of zooplankton were identified from Saheb Bandh, Purulia (Rotifera, Cladocera, Copepoda, and Ostracoda). A total of 25 taxa were recorded (Rotifera 10, Cladocera7, Copepods 5 and Ostracoda 3). Among the Rotiferans, Branchionus sp, and Keratella sp, etc. species; among the Cladocerans, Daphnia sp, Moina sp, and Bosmina sp, etc. species; among Copepodans, Cyclops sp and Mesocyclops sp, etc. species and among the Ostracodans, Candona sp, Heterocypris sp, and cypria sp, etc. species were abundant. The zooplankton in this lake follows a sequence as Rotifera > Cladocera > Copepods > Ostracoda. A correlation was drawn between various physicochemical parameters and zooplankton density. Some changes in zooplankton community structure are related to seasonal changes in water temperature, ph, hardness, alkalinity, and nutrient content in the water. Increased levels of Dissolved Oxygen (DO) and nutrients such as nitrates, and phosphates indicate favorable conditions for the growth of zooplankton. This study showed that the presence of the aforementioned species is considered a biological indicator of eutrophication.